Numerical Investigations of Infrared Slot Waveguides for Gas Sensing - Christian Ranacher (Proceedings, 2018)
Sensing of gases is a promising area for applications of photonic sensor devices that operate in the mid-infrared spectral range. We present a numerical investigation of slot waveguides for evanescent field sensing of CO2. The sensor platform is a poly-silicon slot waveguide on silicon dioxide, where both layers are deposited on a standard silicon substrate. The evanescent field ratio, which is a crucial parameter for the sensing performance of the waveguides, was determined and values as high as 42% were obtained.